Reconciling the Carbon Balance of Northern Sweden Through Integration of Observations and Modelling. Issue 23 (29th November 2021) - Sathyanadh, Anusha; Monteil, Guillaume; Scholze, Marko; Klosterhalfen, Anne; Laudon, Hjalmar; Wu, Zhendong; Gerbig, Christoph; Peters, Wouter; Bastrikov, Vladislav; Nilsson, Mats B.; Peichl, Matthias
Abstract: The boreal biome plays an important role in the global carbon cycle. However, current estimates of its sink‐source strength and responses to changes in climate are primarily derived from models and thus remain uncertain. A major challenge is the validation of these models at a regional scale since empirical flux estimates are typically confined to ecosystem or continental scales. The Integrated Carbon Observation System (ICOS)‐Svartberget atmospheric station (SVB) provides observations including tall tower eddy covariance (EC) and atmospheric concentration measurements that can contribute to such validation in Northern Sweden. Thus, the overall aim of this study was to quantify the carbon balance in Northern Sweden region by integrating land‐atmosphere fluxes and atmospheric carbon dioxide (CO2 ) concentrations. There were three specific objectives. First, to compare flux estimates from four models (VPRM, LPJ‐GUESS, ORCHIDEE, and SiBCASA) to tall tower EC measurements at SVB during the years 2016–2018. Second to assess the fluxes' impact on atmospheric CO2 concentrations using a regional transport model. Third, to assess the impact of the drought in 2018. The comparison of estimated concentrations with ICOS observations helped the evaluation of the models' regional scale performance. Both the simulations and observations indicate there were similar reductions in the net CO2 uptake during drought. All the models (except for SiBCASA) and observations indicated the region was a net carbon sink during the 3‐year study period. Our study highlights a need to improve vegetation models through comparisons with empirical data and demonstrate the ICOS network's potential utility for constraining CO2 fluxes in the region. Plain Language Summary: As the largest global carbon sink, the boreal region can play an important role in climate mitigation strategies. Thus, it is important to estimate the region's sink strength properly. However, due to limitations in measurement techniques at the regional scale, the sink strength estimates are often obtained from models, which require robust validation. Therefore, we combined flux and atmospheric concentration data from one of the stations in Northern Europe to validate estimates generated using four vegetation models. We also used a transport model to connect the fluxes to atmospheric concentration dynamics, then compared the modeled CO2 concentration patterns with observations to provide a regional scale validation of the vegetation models. These observed and modeled fluxes and concentrations are also used to investigate the impact of the 2018 drought over Nordic vegetation. We find that the 2018 European drought had only limited impact on the carbon fluxes over Northern Sweden. Both the modeling and measurements show that the study region was a carbon sink during the study period (2016–2018), with some variation in estimates from the four models. Key Points: Northern Sweden region was a carbon sink in the years 2016–2018 according to vegetation model estimates and observations Both concentration and flux measurements suggest 2018 drought had limited impact on the Nordic carbon balance Empirical measurements can improve vegetation models by integrating them into model simulations at site and regional scale However, annual net ecosystem exchange values generated by the models varied between −275 and −25 gC m − 2 year − 1